The Role of Policy in Promoting Efficient and Quality Discipline Reform. Issue 2 (1st June 2018) - Fergus, Edward
Abstract: The current policy terrain is primed for schools to absorb new discipline strategies and address bias-based beliefs. Over the past 10 years, numerous policy changes regarding discipline have emerged at the federal and state levels. I argue these policy shifts, primarily at the state level, are using two of four value levers (quality, efficiency, choice, and equity) identified in research as the impetus for policy development. I focus on the quality and efficiency levers, as I believe these have been central to the recent changes in discipline policy. Quality is defined in terms of optimal educational experiences, such as instructional time, rehabilitative discipline, and appropriate behavioral interventions based on age. This quality frame suggests that behavioral interventions should not jeopardize instructional time or be inappropriate toward children. Another basis for policy shifts, the efficiency frame, implies effective behavioral interventions are used at an appropriate and effective level. In sum, discipline policy shifts, whether based on a quality and/or efficiency frame, can potentially make room for schools to consider other approaches for addressing student behavior.